Value individualism and the popular-choice theory of secession - Cavallero, Eric (Social Theory and Practice, 2017)
Keywords: dept.phi

Opportunity and responsibility for health - Cavallero, Eric (The Journal of Ethics, 2019)
Wealth and income are highly predictive of health and longevity. Egalitarians who maintain that this “socioeconomic-status gradient” in health is unjust are challenged by the fact that a significant component of it is owed to the higher prevalence of certain kinds of voluntary risk-taking among members of lower socioeconomic groups. Some egalitarians have argued that these apparently free personal choices are not genuinely free, and that those who make them should not be held morally responsible for the resulting harms to their health. I argue to the contrary that such choices usually are fully free, and that those who make them are responsible for their consequences. This does not imply, however, that society cannot also be responsible for those consequences. It is responsible for them if they are statistically foreseeable and avoidable outcomes of unjust public institutions and policies. I show that many of the harms to health that contribute to the voluntary behavioral component of the SES health gradient satisfy that description. Society can therefore be morally responsible for those harms, even though the individuals who suffer them are also fully responsible for them.
Keywords: Equality of opportunity; Health; Personal responsibility; SES gradient in health; Social responsibility; dept.phi; peer-reviewed

Association and asylum - Cavallero, Eric (Philosophical Studies, 2014)
Keywords: dept.phi

Health, luck and moral fallacies of the second best - Cavallero, Eric (The Journal of Ethics, 2011)
Individuals who become ill as a result of personal lifestyle choices often shift the monetary costs of their healthcare needs to the taxpaying public or to fellow members of a private insurance pool. Some argue that policies permitting such cost shifting are unfair. Arguments for this view may seem to draw support from luck egalitarian accounts of distributive justice. This essay argues that the luck egalitarian framework provides no such support. To allocate healthcare costs on the basis of personal responsibility would arbitrarily and publicly burden socially detectable risk-takers while undetectable risk-takers continue to get a free ride. That problem is unavoidable even on the assumption that distributive institutions outside the healthcare sector are fully just. In actual, farfrom-just societies, imposing personal liability for the costs of voluntary risk taking would be wrong for an additional reason. Doing so would tend to magnify existing distributive injustices. These conclusions draw attention to two common 'moral fallacies of the second best' that can arise when applying ideal normative theory to matters of institutional design and in real-world policy contexts. © 2011 Springer Science+Business Media B.V.
Keywords: Egalitarianism; Health; Healthcare; Luck; Luck egalitaianism; Personal responsibility; Responsibility; dept.phi; peer-reviewed

Coercion, inequality and the international property regime - Cavallero, Eric (Journal of Political Philosophy, 2010)
Keywords: dept.phi